Child Custody Rights for Mothers of Different Religions: Maqāṣid al-Sharī'ah Perspective on Islamic Family Law in Indonesia - Mera, Nasaruddin; Marzuki, Marzuki; Taufan B., M.; Sapruddin, Sapruddin; Cahyani, Andi Intan (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Marriage is a physical and mental bond between a man and a woman. It is hoped that it will give birth to a harmonious and happy family, including having offspring who will then care for them well. In reality, couples from different religions who later divorce and have children become a problem, because custody becomes a struggle between the father and mother. This research discusses the child custody rights of an apostate mother as happened in the Parigi religious court decision case, Central Sulawesi. This study uses empirical legal methods with a maqāṣid al-sharī'ah approach. The data collection techniques used were interviews and document study. The informants interviewed were judges, academics and ulama. The documents analyzed were religious court decisions, journal articles, legal rules and books related to the discussion. The results of the research show that in deciding cases, the panel of judges set aside the written law which was used as a reference, and the compilation of Islamic law in order to fulfill the principle of benefit from fulfilling legal objectives. There are several reasons for the judge to overrule these two laws: the interests of the child, social aspects, the principle of benefit (mashlahat) for all. In the end, the judge's decision within the framework of maqāṣid al-sharī'ahanalysis has implications for the maintenance of the soul, eyesight, and the maintenance of offspring, as well as the maintenance of religion.